Effectiveness of Information and Communication Technology (ICT) Tools used during Covid-19Pandemic for Malaysian Construction Projects - Anak Jane, Morris; Nagapan, Sasitharan (Recent Trends in Civil Engineering and Built Environment, 2022)
Construction is an important industry that contributes significantly to a country's economic growth, especially in Malaysia. The construction industry is an organization who constructs, renovates, and refurbishes a building, infrastructure, or structure. During, Covid-19 pandemic, the traditional construction method faces many challenges, such as difficulties communicating with all workers smoothly. The poor communication on the construction sites is the misunderstanding between superiors and workers, misinterpreting instructions, and poor communication skills among workers. This study aim to discover the effectiveness of Information and Communication Technology (ICT) tools used during Covid-19 pandemic on the delivery of information communication among the construction team in Malaysia. The data is collected using questionnaires surveys all over Malaysia. The collected data are analyzed using SPSS software to produce and finalize final data. The result shows that 59.7% of the respondents mostly used AutoCAD and shows 50% of respondents respond to the challenges of the Covid-19 crisis through Building Information Modeling (BIM). The findings of the study revealed 43.5% of respondent agreed that ICT tools is very effective. The study able to benefits construction workers and managers by using ICT tools to improve communication problems during this pandemic.